This question involves composition functions where (f o g)(x) = f(g(x))
For your specific question (f o g)(x) where f(x)= x^3; g(x)= 5x^2
(f o g)(x) = f(g(x))
substitute 5x^2 in for x in f(x)= x^3 = (5x^2)^3
cube the entire expression = (5^3)(x^2)^3
simplifying and #using rule of exponents = 125x^(2*3)
NOTE: # Here you needed to use the rule of exponents: (a ^b)^c = a^(b*c)
When a base is raise to an exponent is raised to another exponent, the exponents are multiplied.
ANSWER: (f o g)(x) = 125x^6
Victor, I hope you have a better understanding of the process for composition functions.